Household governance and time allocation: Structures and processes of social control in Dutch households - Philip Wotschack (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2005)
This article introduces the concept of 'household governance' and investigates empirical differences in governance practices among Dutch households. It stresses informal household rules and conflict-handling strategies of cohabiting couples as important means to govern daily time allocation. The leading question is to what extent the concept of household governance contributes to our understanding of the way households combine the demands from paid and unpaid work. Empirical analyses based on a sample of 809 Dutch cohabiting employees and their spouses (Time Competition Survey 2003) show considerable differences in the use of household rules and conflicthandling strategies among households. A linear regression analysis confirms that the demand to govern daily time allocation by means of household rules and conflicthandling strategies is influenced by the earner type of the household, household characteristics (e.g. the presence of children) and job demands (e.g. frequent requests for working overtime). In this context, the interaction of household demands and job demands plays a major role for the type of household governance that is used in the household. Moreover, we found characteristic differences in conflict handling between men and women. – – Ziel des Artikels ist es, Idee und Konzept der 'household governance' vorzustellen und empirische Unterschiede in den Steuerungspraktiken niederländischer Haushalte zu untersuchen. Zentrale Elemente des Konzeptes sind einerseits informelle Vereinbarungen von Paaren, um die Verteilung bezahlter und unbezahlter Arbeit zu regulieren, andererseits Strategien von Paaren, um interpersonelle Konflikte bei der täglichen Aufgabenteilung zu bewältigen. Dabei ist die Frage leitend, inwieweit das Konzept der 'household governance' zum besseren Verständnis darüber beiträgt, wie Paare die Anforderungen aus bezahlter und unbezahlter Arbeit vereinbaren. Die empirische Analyse basiert auf einer Stichprobe von 809 niederländischen zusammenlebenden Paaren (Time Competition Survey 2003). Sie zeigt deutliche Unterschiede bei der Nutzung informeller Haushaltsregeln und Konfliktbewältigungsstrategien bei den von uns untersuchten Paaren. Eine lineare Regressionsanalyse bestätigt, dass der Regulierungsbedarf der Haushalte dabei von der Haushalts- und Arbeitssituation der Paare abhängt, etwa dem Vorhandensein von Kindern oder hohen Anforderungen aus dem Erwerbsbereich. In diesem Zusammenhang ist das Zusammenspiel von Anforderungen aus der Haushalts- und Erwerbssphäre von wesentlicher Bedeutung. Darüber hinaus zeigen sich charakteristische Unterschiede im Konfliktverhalten von Männern und Frauen.
Keywords: 300; Haushaltsökonomik; Familienökonomik; Niederlande; Governance-Ansatz